Strategi Self Regulated Learning dan Prestasi Belajar: Kajian Meta Analisis - Latipah, Eva (Faculty of Psychology, Universitas Gadjah Mada, 2010)
This article presents a metaâ€analysis of the experimental and survey literature that has examined the effect of self regulated learning strategies on academic achievement. The result of meta analysis on 14 effects sizes from 3899 subjects show that self regulated learning strategies is positively correlated to academic achievement (r = 0.26). The difference in variance of correlation can, among others, be caused by sampling error (4.63%) and error in measurement of independent as well as dependent variables (4.44%). This small percentage shows that error deviation probably caused by sampling error and error in measurement of independent and dependent variables was very small. Result indicated that self regulated learning strategies positively influence studentsâ€™ academic achievement.